2016
DOI: 10.1002/cctc.201501399
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of 2,3‐Butanediol over Phosphate Catalysts

Abstract: 2,3‐Butanediol (BDO) is an excellent feedstock for expanding the network of bio‐based chemicals through catalytic technologies. The dehydration of BDO provides an alternative green route to important chemicals such as methyl ethyl ketone (MEK) and 1,3‐butadiene (BD). In this contribution, we report on the catalytic performance of boron (BP), aluminum (AlP), titanium (TiP), zirconium (ZrP), and niobium (NbP) phosphates in BDO dehydration. The kinetic study points to three reaction pathways operating over phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…This could be done with non‐zeolite catalysts to eliminate the risk of irreversible catalyst deactivation while operating in aqueous media. Successful dehydration of 2,3‐BDO to MEK (1 st step) has been reported over strong acid catalysts such as Nafion‐H and phosphate catalysts . Bucsi et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be done with non‐zeolite catalysts to eliminate the risk of irreversible catalyst deactivation while operating in aqueous media. Successful dehydration of 2,3‐BDO to MEK (1 st step) has been reported over strong acid catalysts such as Nafion‐H and phosphate catalysts . Bucsi et al.…”
Section: Introductionmentioning
confidence: 99%
“…reported 80 % yield of MEK over Nafion‐H while operating at 175 °C . More recently, 78 % yield of MEK was achieved over aluminum phosphate at reaction temperature of 250 °C . 2,3‐BDO can also be directly converted into MEK using sulfuric acid (H 2 SO 4 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the noted compounds are of particular interest as renewable feedstocks for the production of chemicals. The majority of studies on 2,3-BD conversion are dedicated to its dehydrative conversion that yields methyl ethyl ketone (MEK) and isobutyraldehyde [9][10][11][12], 3-butene-2-ol [10,[13][14][15], butenes [16][17][18] and 1,3-butadiene [19][20][21]. Some 2,3-BD derivatives have been previously considered as potential motor fuel components and organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…In the dehydration of 2,3-BDO, 2-butanone (MEK) can be produced easily in acidic aqueous solution [8,9], over several acid solid catalysts such as bentonite [7], alumina [10,11], silica-alumina [11], heteropoly acids [12], and zeolites [13][14][15][16][17][18]. As described in Scheme 1, the hydroxyl group on the 2-position of 2,3-BDO can be easily captured by a proton or an acidic site, and dissociated.…”
Section: Introductionmentioning
confidence: 99%
“…However, when combining the two types of acid sites together, heavy products increased rapidly [18]. It has been also observed that high carbon balance and low coke formation can be obtained via diluting the reactant 2,3-BDO with an appropriate amount of water [10].…”
Section: Introductionmentioning
confidence: 99%